Perlindungan Hukum Rahasia Dagang Pelaku Usaha Terkait Pelaksanaan Sertifikasi Halal di Kota Makassar (Hasanuddin Civil and Bussiness Law Review, 2026)
In this modern era, trade secrets play a crucial role in the world of commerce. Therefore, this information must be kept confidential to prevent it from being leaked to other parties. On the other hand, food and beverage businesses are required to have a Halal Certificate, as a manifestation of the Halal Product Guarantee Law, which examines raw materials, production processes, the implemented Halal Assurance System, location, equipment, and distribution and presentation of products. This raises concerns among business owners regarding the protection of their trade secret information, as this information can determine the success or failure of a business. The purpose of this study is to determine the responsibilities of BPJPH (Indonesian Food and Beverage Supervisory Agency) in implementing Halal certification related to the protection of business secrets, and to determine the efforts that business owners must take to ensure their trade secrets are legally protected. This research is an empirical study. Data collection techniques used were field research and literature study. Field research was obtained through interviews with the Halal Inspection Institution (LPH) and business owners, while literature study research was obtained from laws and regulations, scientific articles, and other written sources. The results of the study show that: (1) BPJPH, in implementing halal certification of food and beverages in Makassar City, must ensure that sensitive information, such as recipes and production processes, are kept confidential by auditors or related parties, to avoid misuse of data by unauthorized parties, considering that there are concerns that business actors, as owners of trade secrets, will not protect their trade secrets, which have strategic value and competitive advantages, so that they must be responsible if there is a violation of the business actor's trade secrets; (2) Efforts that can be made by business actors, if there is a violation of trade secrets, are to file a civil.
Keywords: Makassar; Trade Secret; Halal Certificate